Highly transparent triboelectric nanogenerator utilizing in-situ chemically welded silver nanowire network as electrode for mechanical energy harvesting and body motion monitoring. (May 2019) - Liang, Xianwen; Zhao, Tao; Jiang, Wen; Yu, Xuecheng; Hu, Yougen; Zhu, Pengli; Zheng, Hairong; Sun, Rong; Wong, Ching-Ping
Abstract: Triboelectric nanogenerators (TENGs) functioning as energy harvester as well as body motion sensor pose great significance for oncoming wearable (opto)electronic systems. Herein, A transparent welded AgNW electrode based TENG (WA-TENG) is demonstrated. AgNWs are in-situ chemically welded with surfacial silver oxide naturally formed in air as solder and hydrazine as reductant based on epitaxial recrystallization, ensuring high transparency and conductivity of the electrode used in TENG. This welding endows AgNW electrodes with a high transmittance of 96% (at 77 Ω/sq sheet resistance) and low sheet resistance of 18 Ω/sq (at 92% transmittance), meanwhile, can effectively heal the damaged AgNW network. The WA-TENG exhibits a transmittance up to 95%, and generates an open-circuit voltage ( V oc ) of 66 V, short-circuit current ( I sc ) of 8.6 μA, and peak power density of 446 mW/m 2 under single-electrode mode at 2 Hz. Besides, it can be employed to monitor human body motions, including bending of the elbow, eye blinking, and bending angle and frequency of the finger. Lastly, the WA-TENG serves as a tactile sensor to record touch control of a smart phone by the finger. The WA-TENG with standout transparency, electric output and sensing performance underscores the crucial role in self-powered wearable multifunctional devices. Graphical abstract: Image 1 Highlights: Highly transparent TENG with in-situ chemically welded AgNW network as electrode. The welding endows AgNW electrodes with high transmittance and conductivity. The transparent TENG shows outstanding transparency and electric output performance. The transparent TENG exhibits excellent human body motion sensing performance. The transparent TENG acts as tactile sensor to record touch control of smart phone.